Penerapan Akad Salam pada Sistem Pre-Order Marketplace: Studi Kritik Keabsahan Transaksi - Hasyim Mustofa; Munawir Munawir (AHKAM, 2026)
Although Islamic contracts for deferred delivery transactions have been widely studied, research that critically analyzes the validity of Pre-Order (PO) mechanisms on digital marketplace platforms from the perspective of Islamic commercial jurisprudence remains limited. This study aims to analyze the compatibility of PO transactions in digital marketplaces with the provisions of the Salam contract in classical Islamic jurisprudence. This study used a normative juridical approach through library research by analyzing primary sources in the form of classical fiqh texts, DSN-MUI fatwas, and contemporary Islamic economics studies. The data were analyzed using descriptive-analytical content analysis on three dimensions, namely the pillars and conditions of the Salam contract, the legal position of the marketplace as a third party, and the cancellation mechanism and delivery time provisions. The results showed that PO transactions structurally resemble the Salam contract, but the Down Payment (DP) system commonly applied has the potential to violate the prohibition of bay’ al-kali’ bil kali’. However, if the marketplace is positioned as the seller’s agent through an escrow system, the requirement of cash payment in advance can be fulfilled. The conclusion of this study affirms that full payment and clear product specifications are the minimum requirements for Salam contract compliance in PO transactions on marketplaces. The implications of this study provide theoretical contributions to the development of Islamic e-commerce jurisprudence and practical recommendations for marketplace governance based on sharia principles that are more consistent with the principles of Islamic commercial jurisprudence.